Pengaruh Kepemimpinan Transformasional Kepala Sekolah Terhadap Peningkatan Kinerja Guru-guru SMAK Ebenezer Hutabalang Kecamatan Badiri Kabupaten Tapanuli Tengah Tahun 2023 - Juli Sastra Sitanggang; Haposan Silalahi; Maringan Sinambela; Meditatio Situmorang; Grecetinovitria Butarbutar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The study aims to determine whether there is an influence of the Principal's transformational leadership on improving the performance of teachers at SMAK Ebenezer Hutabalang. The research hypothesis is that there is a positive influence between the transformational leadership of the Principal on improving the performance of teachers at Ebenezer Hutabalang High School in 2023. This research method is quantitative. The population of all teachers at Ebenezer Hutabalang High School in 2023 amounted to 20 people. Sampling is the entire population so that this research is population research. The research instrument was a closed questionnaire. The results of the analysis requirements obtained the value of rxy = 0.631> table = 0.444 indicate a positive relationship between the transformational leadership of the Principal with teacher performance and obtain a regression equation. Hypothesis testing obtained Fhitung = 11.92> Ftabel = 3.55 then H0 is rejected and Ha is accepted. The study concluded that there is a positive influence between the transformational leadership of the Principal on improving the performance of teachers at Ebenezer Hutabalang High School in 2023 by 39.82%.